Antibiotic production and growth inhibiting activities on fruit rot fungus of antagonistic Bacilis in citrus - Thanong Narawitseree (Prince of Songkla University Faculty of Science (Biochemistry), 2013)
Thesis (M.Sc., Biochemistry)--Prince of Songkla University, 2010